Review on Developments and Progress in Nickelate‐Based Heterostructure Composites and Superconducting Thin Films. Issue 1 (14th November 2022) - Yang, Xiaoping; Li, Miao; Ding, Zhenyu; Li, Liangyu; Ji, Ce; Wu, Gang
Abstract: In the past decade, the rapid development of modern heterointerface growth and characterization techniques has stimulated great effort to research and design the extraordinary physical properties of transition metal heterostructure composite materials. Here, new physics originates from the rearrangement of orbital, charge, spin, and lattice and the resulting rebalancing of their mutual interactions. In this paper, recent experimental and theoretical progress in the design, preparation, characterization, and physical property measurement of LaNiO3 ‐based heterostructure composites and the infinite‐layer Ni 1 + nickelate superconducting thin films on (001) SrTiO3 substrate is reviewed, mainly by the methods of various X‐ray spectroscopy measurements, scanning transmission electron microscopy, and magneto‐transport measurements. In these materials, the electronic structure and orbital occupation around the Fermi level are modified, enabling nickelate‐based composite materials to exhibit new states of matter and physical phenomena, which are absent in the bulk constituents. Their confined structures, superconductivity, orbital polarization, charge transfer, electronic structures, magnetic properties, and X‐ray spectroscopic analysis, are therefore highlighted, aiming at understanding unconventional superconducting mechanisms and designing new high‐ T c superconducting low‐dimensional materials for device applications. Abstract : Unconventional superconductivity (SC) realized in the Sr‐doped ultrathin LaNiO3 /LaMnO3 superlattice and infinite‐layer R NiO2 ( R = Nd, Pr, La) thin films on SrTiO3 substrate is a breakthrough in nickelate‐based high‐ T c SC research and artificial hetero‐grown superconducting materials. Their multi‐band electronic structure, Mott–Hubbard character, and uncertainty of antiferromagnetic order, etc., are much different from cuprate bulk SC materials.